A hybrid electrochemical-colorimetric sensing platform for detection of explosives - Forzani, Erica S. (2009)
A highly selective, sensitive, and low-cost hybrid sensing platform is developed based on extraordinary properties of explosives in an ionic liquid and an integrated electrochemical and colorimetric approach.